PENGARUH PERSEPSI RISIKO DAN KEPERCAYAAN TERHADAP PALTFORM DIGITAL DALAM KEPUTUSAN BERINVESTASI SAHAM ONLINE - Fadali Rahman; Muhammad Herman Djaja; Dain Lestari; Sitti Aisyah Legenda; Syindina Anansyah Fitriani (Jurnal Riset Multidisiplin Edukasi, 2025)
This study discusses the dynamics of risk perception in investment decision-making by the millennial generation, particularly in the context of digital investments. In general, risk perception plays a significant role in increasing investors' awareness of potential losses, especially for those with a good understanding of risk and financial literacy. However, the findings indicate inconsistencies when investment decisions are made through digital platforms. Overconfidence in technology, the influence of social media, app gamification, and expectations of quick profits lead some millennials to overlook real risks. Risk perception is also influenced by factors such as personal experience, educational and economic background, as well as information disseminated through social media algorithms. The phenomenon of herding behavior further reinforces impulsive decision-making without thorough risk analysis. Therefore, an integrative approach is needed that includes digital literacy, risk understanding, and financial ethics. The roles of regulators, educational institutions, and digital platforms become important in shaping a safe and sustainable investment ecosystem. This study emphasizes the importance of critical and inclusive education to shape a young generation of investors who are not only technologically literate but also wise, rational, and responsible in facing the ever-evolving complexities of the digital economy.